Hydrogen embrittlement of high-strength marine steel as a weld joint in artificial seawater under cathodic polarization. (April 2022) - Ma, Hongchi; Sun, Liyang; Luo, Hong; Li, Xiaogang
Highlights: The weld metal of E690 weld joint is the most vulnerable zone to hydrogen embrittlement. Dislocation slip bands are prone to initiate hydrogen-induced microcracks. M/A constituents and carbides could induce microvoids and decohesion under dynamic loading and hydrogen charging. Abstract: Hydrogen embrittlement (HE) behavior of E690 high-strength steel as a weld joint was investigated in artificial seawater. The most vulnerable location and microstructure to HE was verified, and the underlying mechanism was clarified. Results showed that the weld metal with granular bainitic microstructure leads to premature fracture of the entire weld joint under slow strain rate tensile testing with in-situ hydrogen charging. Dislocation slip bands (DSBs) could be preferentially developed in this zone, and HE initiation was induced via dislocation–hydrogen interaction because the weld metal had the lowest local strength among the weld joint. Martensite/austenite (M/A) constituents and carbides could also contribute to crack initiation and propagation through microvoid coalescence and decohesion.